'How corporate social responsibility can be integrated into corporate sustainability: a theoretical review of their relationships'. Issue 8 (17th November 2018) - Ashrafi, M.; Adams, M.; Walker, T. R.; Magnan, G.
ABSTRACT: The notion that corporations are expected to have social and environmental performance standards and practices while meeting their financial and legal obligations is commonly referred to as corporate social responsibility (CSR) or corporate sustainability (CS). Previous studies have discussed whether the two terms are converging or should be used as stand-alone concepts. After reviewing the trends in development of CSR and CS, and the various viewpoints on the relationships between the two, we propose a relationship model to better understand how CSR can be integrated into CS as either a transitional stage or ultimate goal for a corporation. This study aims to provide researchers and practitioners with further insights on the adoption of CSR and CS. The model is intended to provide a plausible view of the relationships between CSR and CS to help to lessen the confusion and ease the communication both between and within these fields.